PENERAPAN ANALISIS JALUR (PATH ANALISIS) DALAM PEMBELAJARAN BAHASA ARAB: Hubungan Antara Motivasi Belajar, Kreatifitas, Gaya Belajar dan Profesionalisme Guru Terhadap Prestasi Belajar Bahasa Arab - Suparmanto Suparmanto; Ruwaida Hudatullah (Universitas Islam Negeri Mataram, 2021)
This research at Madrasah Aliyah Darul Muhajirin Praya central Lombok NTB. An educational institution under the Darul Muhajiri Islamic Boarding School (Ponpes). this research used the Path Analysis method conceptually and theoretically, from the concept of analysis, multivariant statistics, to the stages of path analysis modeling, it is expected to provide an understanding of path analysis. In its presentation,the researcher will discuss the relationship between learning motivation, creativity, learning style and teacher professionalism on student achievement. In application, there are several relevant software tools to help statistical analysis of the Structural Equation Model (SEM) and path analysis, namely: AMOS, LISREL, EQS, RAINOVA, and others. The author chose LISREL (Linear Structural Relation) version 9.1 Student Edition because it is easy to use and understand.